Soil residual activity of herbicides applied in post-emergence for grass weed control under two environmental conditions - Sieczkowski Martins Vianna, Geraldo Silvestre (2014)
Two field experiments and two greenhouse bioassays were conducted, respectively, at the EEA/UFRS in Guaíba, RS, Brazil, and at the FA/UFRS in Porto Alegre, RS, during the 1984/85 growing season. The objective was to compare the residual effects in soil of four herbicides applied in post-emergence under two environmental conditions, characterized by sunflower (Helianthus annus L., cv. Contisol 711) seeded at the beginning of September, and soybeans (Glycine max (L.) Merrill, cv. BR-4) seeded at the end of November. Millet (Pennisetum americanum (L.) Leeke) and sorghum (Sorghum bicolor (L.) Moench) were used at greenhouse to determine the soil residual effect of the herbicides from soil samples collected in the field. Evaluations of emergence and dry weight of aerial part of the plants were performed at the greenhouse. The herbicides showed longer soil residual effect in the soybean situation. The herbicide rate affected the soil persistence of haloxyfop and fluazifop. On the other hand, fenoxaprop and sethoxydim were unaffected by variation in rate. The soil persistence of the compounds tested was as follows, in decreasing order: haloxyfop-methyl > fluazifop-p-butyl > fenoxaprop-ethyl = sethoxydim.